Comparison of outcome in medical versus expectant management in unruptured tubal pregnancy with β-hCG 1000-3000 IU/L - Arshad, Sidra; Andeel, Sonia; Asghar, Samia; Hafeez, Sana; Asghar, Sana; Fatima, Naheed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Ectopic pregnancy (EP) is an important cause of maternal morbidity as well as mortality in the 1st trimester. This study was done to compare outcome in medical versus expectant management in patients with unruptured tubal pregnancy having β-hCG 1000-3000 IU/L. Methods: In this randomized controlled trial, 82 (41 in each group) women with tubal ectopic pregnancy (TEP) having β-hCG levels between 1000-3000 IU/L and 18 to 40 years of age were enrolled. Women having non-tubal pregnancy, ruptured ectopic pregnancy, heterotopic pregnancy, hypersensitivity to methotrexate were excluded. Included women were randomly assigned to either Group-A (expectant management) or Group-B (medical management). Outcome was measured after one week and considered successful if patient had β-hCG levels negligible i.e. <10 IU/L and complete resolution on ultrasonography (absence of adnexal mass, pelvic free fluid, gestational sac). Results: Overall mean age was 30.65±6.37 years. The mean gestational age in Group-A was 7.12±2.12 weeks and 7.63±2.41 weeks in Group-B. The mean β-hCG levels in Group-A was 1984.63±515.81 IU/L and 1937.33±519.68 IU/L in Group-B. Outcome was successful in 90.24% in Group-A and 63.41% in Group-B (p-value=0.004). Conclusions: Expectant management is associated with better outcome as compared to medical management in tubal ectopic pregnancy having β-hCG between 1000-3000 IU/L.